Pengaruh Fraud Pentagon Terhadap Fraudulent Financial Reporting - Janice Putri; Prima Apriwenni (Universitas Dharma Andalas, 2022)
Fraudulent financial reporting is an act of fraud by intentionally conduct misstatement(s) of financial statements in order to deceive its users. As one of the goals of the state-owned enterprises (SOE) is to make profits, sometimes the management is motivated to performs fraudulent financial reporting to achieve this goal. This study was conducted to determine the influence of financial target, ineffective monitoring, quality of external auditor, change of auditor, change of directors and frequent number of CEO’s picture in the annual report on fraudulent financial reporting in SOEs. The object of this study were 20 SOEs listed on the Indonesia Stock Exchange for the 2017-2019 period. The results of the wald test showed that the significance value of the financial target which proxied by ROA, ineffective monitoring, quality of external auditor, change of auditor, change of directors, and frequent number of CEO’s picture were all above the significant value of 0.05. Hence, the conclusion of this study is that financial target, ineffective monitoring, quality of external auditor, change of auditors, change of directors and frequent number of CEO’s picture have no influence on fraudulent financial reporting. ABSTRAK Fraudulent financial reporting adalah suatu tindak kecurangan yang sengaja dilakukan melalui salah saji dalam laporan keuangan, dengan maksud untuk menipu penggunanya. Salah satu tujuan dari perusahaan Badan Usaha Milik Negara adalah untuk memperoleh laba. Untuk mencapai laba tersebut manajemen dapat termotivasi untuk melakukan tindak kecurangan dalam pelaporan keuangannya. Penelitian ini bertujuan untuk melihat pengaruh dari target finansial, efektivitas pengawasan, kualitas eksternal auditor, pergantian auditor, pergantian direksi, dan banyaknya foto pimpinan dalam laporan tahunan terhadap fraudulent financial reporting di perusahaan BUMN. Obyek penelitian ini adalah 20 perusahaan BUMN yang tercatat di Bursa Efek Indonesia periode 2017-2019. Hasil dari wald test menunjukkan bahwa nilai signifikansi atas target finansial yang diproksikan oleh ROA, efektivitas pengawasan, kualitas eksternal auditor, pergantian auditor, pergantian direksi dan banyaknya foto pimpinan seluruhnya masih diatas nilai signifikasi 0,05. Kesimpulan yang diperoleh melalui penelitian ini yaitu bahwa target finansial, efektivitas pengawasan, kualitas eksternal auditor, pergantian auditor, pergantian direksi, dan banyaknya foto pimpinan dalam laporan tahunan tidak memengaruhi terjadinya fraudulent financial reporting.